Small reservoirs toolkit - Andreini, Marc; Schuetz, Tonya; Harrington, Larry W. (CGIAR Challenge Program on Water and Food, 2009)
People living in arid areas often experience highly variable rainfall, droughts, floods and have insecure livelihoods. Small multi-purpose reservoirs are a widely used form of infrastructure for the provision of water. They supply water for domestic use, livestock watering, small scale irrigation, and other beneficial uses. Although clusters of reservoirs store significant quantities of water and effect on downstream flows, they have rarely been considered as systems, with synergies and tradeoffs resulting from their numbers and their density.